2011
DOI: 10.1007/s10897-011-9388-3
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Beliefs of African‐Americans Toward Genetics, Genetic Testing, and Sickle Cell Disease Education and Awareness

Abstract: Research among African-Americans indicates this population perceives sickle cell (SCD) to be a serious disease and sickle cell trait (SCT) screening an important intervention. However, studies have consistently demonstrated a lower than desired uptake of SCD education, inadequate knowledge regarding personal and family trait status, and a low perceived susceptibility of giving birth to a child with the disease. We examined general attitudes and beliefs regarding genetics and genetic testing including prenatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 23 publications
3
42
0
Order By: Relevance
“…Most participants had inadequate knowledge particularly on the pattern of inheritance of SCD or trait. This is consistent with previous published US data that demonstrated low knowledge of SCD [14][15][16]. In a study among adults who themselves were sickle cell carriers or who had a child with SCT, Acharya et al [8] reported significant misunderstanding about how SCD is inherited.…”
Section: Discussionsupporting
confidence: 89%
“…Most participants had inadequate knowledge particularly on the pattern of inheritance of SCD or trait. This is consistent with previous published US data that demonstrated low knowledge of SCD [14][15][16]. In a study among adults who themselves were sickle cell carriers or who had a child with SCT, Acharya et al [8] reported significant misunderstanding about how SCD is inherited.…”
Section: Discussionsupporting
confidence: 89%
“…Beyond the fact that the discussion of topics such as newborn screening and prenatal testing is more appropriate for individuals of childbearing age [25], statistics show that in Israel most couples marry during their academic studies [26], and will hopefully have genetic counseling during those years. The undergraduate students' age is therefore the most relevant factor in our analysis of their genetic literacy.…”
Section: Introductionmentioning
confidence: 99%
“…First, the at-risk individuals in the family, if aware of the risk, could benefit from prevention strategies. 4,32 Second, if accurate risk perception of cancer were adopted it could be used as a motivator for adhering to screening programs and healthy behaviour modifications. 4 Finally, participants indicated that they were interested in accessing genetic services, but for reasons unknown to the study team appeared not to have accessed these services.…”
Section: Indigenous Health Indigenous Australians: Cancer Risk and Gementioning
confidence: 99%